PENGATURAN PEMBAYARAN UPAH BAGI TENAGA KERJA YANG DIRUMAHKAN - Prayoga, Gede Agi; Yustiawan, Dewa Gede Pradnya (Kertha Wicara : Journal Ilmu Hukum; Vol 12 No 01 (2022), 2023)
Penelitian ini bertujuan mengetahui bagaimana sistem pengupahan bagi pekerja yang dirumahkan karena Covid-19 serta penyelesaian perselisihan hubungan industri berkaitan pengupahan pekerja apabila tak tercapainya suatu kesepakatan. Metode penelitian ini yakni metode penelitian normatif yang diteliti memakai literatur serta sumber data sekunder. Jika melihat pada UU ketenagakerjaan pasal 93 ayat 1 yang tidak mewajibkan mebayar upah bagi tenaga kerja yang tidak mengadakan pekerjaan yang dimana bertentangan dengan Keputusan Menteri Tenaga Kerja No.104 Tahun 2021 angka 2 yang menyatakan tetap mebayar upah dengan kesepakatan yang telah dilakukan antara pengusaha dan pekerja. Menurut asas “lex posterior derogat legi priori” dimana UU yang baru meniadakan keberlakuan UU lama. Jadi, UU yang berlaku bagi tenaga kerja di PHK yaitu Keputusan Menteri Tenaga Kerja No.104 Tahun 2021. Kata kunci: Tenaga Kerja, Dirumahkan, Pandemi Covid 19 ABSTRACT  Purpose this study is to understand how the wage system functions for workers who have been laid off as a result of the Covid-19 outbreak and, in the event that an agreement cannot be reached, to settle labormanagement conflicts over workers' wages. The normative research approach utilized in this publication is investigated using secondary data sources and literature. When compared to the Decree of the Minister of Manpower No. 104 of 2021 number 2, which states that paying wages is still subject to the agreement that has been reached between employers and employees, the Manpower Act's article 93 paragraph 1 does not require employers to pay wages for employees who do not perform work. According to the legal theory known as lex posterior derogat legi prima, new laws nullify the preceding ones' legal standing. Therefore, the Decree of the Minister of Manpower No. 104 of 2021 is the law that governs workers who have been laid off. Key Words: Manpower, Layoff, Covid 19 Pandemic.